2014
DOI: 10.1021/es5025806
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Steroid Hormones, Phytoestrogens, and Estrogenic Activity across a Swine Lagoon/Sprayfield System

Abstract: The inflow, transformation, and attenuation of natural steroid hormones, phytoestrogens, and estrogenic activity was assessed across the lagoon/sprayfield system of a prototypical commercial swine sow operation. Free and conjugated steroid hormones (estrogens, androgens, and progesterone) were detected in urine and feces of sows across reproductive stages, with progesterone being the most abundant steroid hormone. Excreta also contained phytoestrogens indicative of a soy-based diet; particularly daidzein, geni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 57 publications
(112 reference statements)
0
20
0
Order By: Relevance
“…Fifteen (Bartelt-Hunt et al, 2012) to 28 steroid hormones (Liu et al, 2012a) were measured in at least one runoff sample from cattle farms at levels up to 2470 ng/L. Barn flush and swine farm lagoons in the USA contained relatively high levels of steroid hormones and conjugates including P4 (in urine of sows 2640 ng/L, barn flush 544 ng/L, lagoon 303 ng/L) (Yost et al, 2014). In flush water of Chinese swine farms, P4, medroxyprogesterone and norgestrel occurred up to 3470, 71 and 7080 ng/L, respectively (Liu et al, 2012b).…”
Section: Concentrations and Fate In Animal Farm Wastementioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen (Bartelt-Hunt et al, 2012) to 28 steroid hormones (Liu et al, 2012a) were measured in at least one runoff sample from cattle farms at levels up to 2470 ng/L. Barn flush and swine farm lagoons in the USA contained relatively high levels of steroid hormones and conjugates including P4 (in urine of sows 2640 ng/L, barn flush 544 ng/L, lagoon 303 ng/L) (Yost et al, 2014). In flush water of Chinese swine farms, P4, medroxyprogesterone and norgestrel occurred up to 3470, 71 and 7080 ng/L, respectively (Liu et al, 2012b).…”
Section: Concentrations and Fate In Animal Farm Wastementioning
confidence: 99%
“…During storage of animal waste, concentrations of P4 largely decreased, but were detected in soil even after two months of manure application (Yost et al, 2014). Another study in China showed that farm waste lagoons were not effective in reducing steroids including progestins (Liu et al, 2012a).…”
Section: Fate In the Environmentmentioning
confidence: 99%
“…Additionally, animal manures are commonly land applied as fertilizers in crop fields. As a consequence, veterinary pharmaceuticals and steroid hormones in manures are transported into the environment and their residues have been detected in soil, surface water and groundwater impacted by animal wastes (Bartelt-Hunt et al 2011;Chen et al 2010;Wei et al 2011;Yost et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies by our group have found that E1, a potent steroidal estrogen, is the most abundant estrogen species in waste at this field site (Yost et al, 2013, 2014; Lee et al, 2014). Therefore, this study focuses on E1 as a case study to investigate the characteristics of estrogen runoff and transport from AFO spray fields.…”
Section: Introductionmentioning
confidence: 61%